Answer:
1) Combine like terms
2) ![\sqrt[3]{x} =3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%20%3D3)
3) cube both sides of the equation
4) ![4\sqrt[3]{27} +8\sqrt[3]{27}=36](https://tex.z-dn.net/?f=4%5Csqrt%5B3%5D%7B27%7D%20%2B8%5Csqrt%5B3%5D%7B27%7D%3D36)
5) 4(3) + 8(3) = 36
Step-by-step explanation:
1) Combine like terms
2) ![\sqrt[3]{x} =3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%20%3D3)
3) cube both sides of the equation
4) ![4\sqrt[3]{27} +8\sqrt[3]{27}=36](https://tex.z-dn.net/?f=4%5Csqrt%5B3%5D%7B27%7D%20%2B8%5Csqrt%5B3%5D%7B27%7D%3D36)
5) 4(3) + 8(3) = 36
Answer:
y = 4x / x = 1/4 y
Step-by-step explanation:
chairs = x ( to find out how many chairs there are you have to take the legs and divide them by 4 )
Legs = y ( to find out how many legs there are you must multiply the amount of chairs by 4 )
This probability is the same as 1-(two different suited cards). Your first card can be any of the 52 cards. Your second card must be any of the 39 different suited remaining 51 cards. So the answer is 1 - (52/52)(39-51). Note: I assumed there was no replacement.
[ ( x + 4 )( x + 5 ) + 4( x + 1 )( x + 5) - 5( x + 1 )( x + 4 ) ] / [( x + 1 )( x + 4)( x + 5 )] = ( x^2 + 9x + 20 + 4x^2 + 24x +20 - 5x^2 - 25x - 20) / [( x + 1 )( x + 4)( x + 5 )] =
( - 2x + 20 ) / [( x + 1 )( x + 4)( x + 5 )] = ( - 2)( x - 10) / [( x + 1 )( x + 4)( x + 5 )]
Answer:
a
Step-by-step explanation: